The Effect of Egg White Addition to Increase the Tensile Strength of Organic Planting Ribbons - Lintang Ayu Rengganingrum; Johan Andoyo Effendi Noor; Lailatin Nuriyah (Natural B, Journal of Health and Environmental Sciences, 2019)
Egg white contains high protein. Egg white acts as supporting matrix as well as adhesive and organic preservation. Organic planting ribbon based on mixture of water hyacinth with banana stalk is a supporting material for planting purpose, especially for rice planting system. This ribbon is in the form of a rice seed filled ribbon. The application of organic rolling tape in rolls and then lengthwise requires a high level of tensile strength so as not to tear easily. Variations of egg white composition are added to the organic planting tape to increase the value of its tensile strength. The tensile strength test was performed by Force Gauge physical properties i.e. shape, modulus, and density to determine density and strength of adding egg white as a matrix amplifier on the organic plant tape filler. Measurements were made by simulating the planting of rice planted with organic tuna with egg white and without egg whites which watered once every five days for sixty days. The results obtained are compared for analysis and drawn conclusions. The best data obtained for the addition of 250 grams of egg whites respectively for the value of tensile strength of 0.112 N / mm (before planting simulation) and 0.058 N / mm (after planting simulation) with the ability to survive around the age of 50 days.